Effect of Different Desensitizing Protocols on Pulp Inflammatory Responses in Whitened Teeth: A Randomized Clinical Trial - Barros, Antonia Patricia Oliveira [UNESP]; de Mendonça, Raissa Pinheiro; Alencar, Cristiane de Melo; Pinheiro, João de Jesus Viana; Rothbarth, Cláudia Pires; Júnior, Sérgio de Melo Alves; Silva, Cecy Martins (Bentham Science Publishers, 2023)
Purpose: This randomized controlled, blind clinical trial evaluated the efficacy of different desensitizing protocols in preventing pulp inflammation after whitening treatment with hydrogen peroxide (HP) at 35% (Whiteness HP 35%). Materials and Methods: Thirty healthy third human molars extracted by orthodontic indication were randomized and allocated into five groups (n=5): NC (negative control): without intervention; PC (positive control): HP; PBM: HP + photobiomodulation with a Watts LASER; CPP: HP + casein phosphopeptide amorphous calcium phosphopeptide (CPP-ACP); and NANO: HP + nano-hydroxyapatite. The in-office whitening was performed in two sessions with a single 45 minutes application at an interval of 48 hours. Pulp tissues were extirpated for immunohistochemical analysis. Immunoreaction for activated caspase-3 was observed, and images were acquired using an Axio Scope A1 microscope. The Kruskal-Wallis test was used to evaluate the immunoexpression of caspase-3. Results: Comparisons between the PC and NC groups revealed a statistically significant difference (p<0.05) for the analysis of caspase-3 immunoexpression. A statistically significant difference (p<0.05) was also observed for the CPP and PBM groups in relation to the PC. Conclusion: Photobiomodulation and CPP-ACP are promising alternatives to minimize pulpal inflammation induced by tooth whitening. Clinical Trial Registration Number: NCT04548674.
Keywords: Caspase-3; Immunohistochemistry; Randomized controlled clinical trial; Sensitivity; Therapies; Tooth whitening